Subprime and euro crisis: Should we blame the economists? - Peter Spahn (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
Economists in the public are accused of propagating highly professional, but unrealistic theories that mislead market agents and policy makers to place too much confidence in rational behaviour and market equilibrium. The paper analyses to what extent the US banking crisis and the euro crisis can be ascribed to fallacious assessments and recommendations on the part of economic theory. In the first case, myopic financial market theory and practice had neglected systemic repercussions of micro bank trading patterns. The euro crisis emerged from the neglect of undergraduate economic wisdom of necessary adjustment mechanisms in a currency union. Economists hopefully misinterpreted current account deficits as a sign of structural change.
urn:nbn:de:bsz:100-opus-8969
Keywords: F33; G20; N10; N20; 330; Efficient Market Hypothesis; rational behaviour; banking crisis; New Keynesian model; intertemporal optimisation; euro crisis